The Influence of Work Motivation and Work Atmosphere on the Performance of Public Works and Spatial Planning Department Employees in Selayar Islands Regency - Amri Muammar; Dg Maklassa; Sitti Nurbaya (Pustaka Digital Indonesia, 2024)
The aim of the research is to determine the influence of work motivation and work atmosphere on the performance of employees of the Selayar Islands Regency Public Works and Spatial Planning Service. This is a type of quantitative research. This sample was taken from the Selayar Islands Regency Public Works and Spatial Planning Office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 25 application regarding the influence of work motivation and atmosphere on the performance of employees of the Selayar Islands Regency Public Works and Spatial Planning Service, work motivation has a significant positive effect on employee performance with a value of Tcount is 2.294 > 1.689 and the sig value. 0.028 < 0.05. Work atmosphere has a significant negative effect on employee performance with a T value of -2.343 > 1.689 and a sig. 0.025 < 0.05. Work motivation and the existing work atmosphere must be further improved and maintained because it can be seen from the research results that the existing work motivation and work atmosphere are still quite normal and stable.